Early Cambrian (Marianian) trilobites and associated faunas from the Sierra Norte de Sevilla Geopark: A scientific and heritage approach. - Eduardo Mayoral Alfaro; Eladio Liñán; Rodolfo Gozalo; Jose Antonio Gámez Vintaned; María Eugenia Dies Álvarez; Luis Collantes Ruiz; Ana Santos; Alberto Gil-Toja (Geoconservation Research)
Some exceptional paleontological trilobite sites located in the Sierra Norte de Sevilla UNESCO Global Geopark are presented herein, together with an analysis of their geotourism / geotrail potential and a proposal for geoconservation. The sites are of Marianian age, a regional stage and age of the Cambrian Mediterranean Subprovince which was defined within the territory of the Geopark. This area constitutes the type area of six trilobite genera and twelve trilobite species and other associated faunas (hyolith, serpulid and echinoderm species).